POWDER FORMULATION OF ANTAGONISTS YEASTS, Cryptococcus albidus AND Cryptococcus terreus AS BIOFUNGICIDES - Suryo Wiyono (SEAMEO BIOTROP, 2013)
The research has following objectives: 1) to investigate compatibility of yeasts antagonist C. albidus and C. terreus, 2) to obtain suitable carrier in powder formulation for those two yeasts, 3) to get appropriate formulation additives for those yeasts, and 4) to obtain optimum powder formulation consisting yeasts, carrier materials and additives. Compatibility of C. albidus and C. terreus was tested through bio-assay against Lasiodiplodia theobromae on detached banana fruit and Alternaria solani on detached tomato leaves. Compatibility was indicated by no reduction of antagonistic activity. Benomyl-resistant mutant of C. albidus and cycloheximide-resistant mutant of C. terreus were mixed with sterilized tapioca, talc and kaolin to get initial yeasts density of 8.5 log cfu/g and water content of 15%, then packed by plastic bag and stored under room temperature. Survival of formulated yeasts was assessed monthly by plating on PDA medium containing 150 ppm cycloheximide for C. terreus, and 150 ppm benomyl for C. albidus. Yeasts population was expressed in log cfu/g materials. To determine effect of carrier materials on antagonistic activity, bio-assay of formulated yeasts against pathogens was conducted after 3 months storage. Tested additives i.e. CaCl2, pure chitin and crab shell powder were added into suspension of C. albidus and C. terreus to get concentration of 1.25%, 0.5 % and 0. 1% (w/v). Sterilized aquadest and yeasts without additives was used as control. Then the treatments was examined the antagonistic activity through bio-asaay on detached banana fruits and tomato leaves. Appropriate additive(s) was determined by its ability to increase antagonistic activity of yeasts. Storability and antagonistic activity of C. albidus dan C. terreus in the mixture of best carrier and additive were examined. C. terreus was compatible to C. albidus. The best carrier materials supporting highest survival of C. terreus was tapioca and talc, those supported survival for four months storage. Talc was best carrier material for C. albidus formulation by maintaining its survival for five months storage. Additives which able to increase antagonistic activity of C. terreus were CaCl2 0.1 % , pure chitin 0.1 % and crab shell powder 0.5%. Additives providing best increase of antagonistic activity of C. albidus were CaCl2 0.5%, pure chitin 1.25 % and crab shell 1.25%. Supplementation of chitin and crab shell, both at the rate of 1.25% into talc-base powder formulation increased survival of both yeasts at one months storage, however no significant effect subsequently.Key words: formulation, yeasts antagonists, Cryptococcus terreus, Cryptococcus albidus, carrier agent, talc, tapioca, kaolin, CaCl2, chitin, crab shell powder